PENGARUH DESAIN PRODUK KELENGKAPAN PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK EIGER DI SEMARANG - Juliana Devi Purnama Putri, 15.05.51.0263; Setiawan, Mulyo Budi (Students' Journal of Economic and Management, 2019)
This research aims to determine how much influence the product design, product completeness, and price on the purchasing decision of EIGER products in Semarang. And this research also aims to analyze the most dominant factors affecting purchasing decisions on EIGER products in Semarang. The population used in this study is consumers who buy EIGER products in Semarang. The sample in this study were 100 respondents and the technique used was a non-probability sampling technique with a purposive sampling approach (sampling based on certain considerations). The analytical method used is quantitative analysis, namely multiple regression analysis. Based on the t test, it can be seen that the complete product and price variables have a positive and significant effect on purchasing decisions while the product design variables have a positive and not significant effect on the purchasing decisions of EIGER products in Semarang.